Elena et Les Hommes or Paris Does Strange Things: Eros and Eris in Jean Renoir Reception of Helen of Troy - de Miranda N. Coelho, Maria Cecília (Nuntius Antiquus, 2022)
This article is part of a broader research project on the reception of Helen of Troy in cinema. Here, I present an analysis Elena et les hommes, also known by the English title Paris Does Strange Things, directed by Jean Renoir. Released in 1956, during the Algerian War of Independence (1954-1962), the film fictionalizes an episode in the life of French General Georges Boulanger (1837-1891), making him one of the suitors of a beautiful Polish princess named Elena Sorokovska. I argue that the French director constructed his protagonist by transplanting to the screen literary material related to the version of Helen of Troy found in Euripides’ Helen, a work that is also often interpreted as presenting a pacifist perspective.